Modified augmented fractional order control schemes for cart inverted pendulum using constrained Luus-Jaakola optimisation. (10th June 2022) - Mukherjee, Deep; Raja, G. Lloyds; Kundu, Palash; Ghosh, Apurba
Since the upright position of an inverted pendulum system is an unstable equilibrium, it is extremely challenging to control. Fractional order based control schemes are becoming increasingly popular in stabilising an unstable system and achieving satisfactory closed-loop performance. Therefore, a novel combination of fractional order Lyapunov (FOLyapunov) rule and fractional order proportional integral (FOPI)/two-degree of freedom FOPI (2DOF-FOPI) controller is proposed to tackle this problem. Parameters of FOPI/2DOF-FOPI controllers are obtained using multi-objective constrained Luus-Jaakola multipass optimisation method. Comparative simulation studies are carried out with direct synthesis based PID control scheme, combination of fractional order Massachusetts Institute of Technology (FOMIT) rule augmented with either FOPI/2DOF-FOPI controllers using a mathematical model of inverted pendulum. It is evident that the proposed combination of FOLyapunov method and FOPI/2DOF-FOPI controllers outperforms the other schemes.